2009
DOI: 10.1212/01.wnl.0000342471.07290.07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac complications on outcome after aneurysmal subarachnoid hemorrhage

Abstract: Markers for cardiac damage and dysfunction are associated with an increased risk of death, poor outcome, and delayed cerebral ischemia after subarachnoid hemorrhage. Future research should establish whether these cardiac abnormalities are independent prognosticators and should be directed toward pathophysiologic mechanisms and potential treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 38 publications
(28 reference statements)
5
92
2
3
Order By: Relevance
“…An acute increase in troponin levels after SAH is a risk factor for cerebrovascular and cardiopulmonary complications (4). In a 253 patient SAH case series, serial troponin level measurements were performed and ECG controls were maintained to demonstrate the cardiac damage, and increased peak troponin levels were found to be related to left ventricular disfunction, pulmonary edema, hypotension in need of vasopressor support (as in our case), and increased cerebral ischemia related to vasospasm (10).…”
Section: Discussionsupporting
confidence: 51%
“…An acute increase in troponin levels after SAH is a risk factor for cerebrovascular and cardiopulmonary complications (4). In a 253 patient SAH case series, serial troponin level measurements were performed and ECG controls were maintained to demonstrate the cardiac damage, and increased peak troponin levels were found to be related to left ventricular disfunction, pulmonary edema, hypotension in need of vasopressor support (as in our case), and increased cerebral ischemia related to vasospasm (10).…”
Section: Discussionsupporting
confidence: 51%
“…This finding is in line with those of earlier studies considering that measurements were taken on different days. 26,28 The fact that the serum NT-proBNP levels were highest after 3 days in patients with SAH and aneurysms argues, though, that the initial cardiac injury is not solely responsible for the increased levels. Other events during these days probably also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with clipped aneurysms had a higher incidence of poor functional outcome at discharge (69.4% versus 51.4% of patients in clipped and coiled patients, respectively; PϽ0.0001) and mortality (at discharge: 14.6% versus 9.1% in clipped and coiled patients, respectively, Pϭ0.01; 30 days after SAH: 13 …”
Section: Comparison Of Outcome Parametersmentioning
confidence: 99%
“…8,11 A recent meta-analysis in patients with SAH showed that markers of cardiac damage and dysfunction are associated with poor outcome and mortality. 13 Damage to the insular cortex in patients with stroke has been associated with electrocardiographic abnormalities. 8 The results of our study have implications for daily practice.…”
Section: Vergouwen Et Al Complications After Clipped and Coiled Aneurmentioning
confidence: 99%